Difference and punishment: Ethno-political exclusion, colonial institutional legacies, and incarceration - Davis, Andrew P. (Punishment & society, 2020)
One dominant theoretical explanation for higher incarceration rates across the world focuses on how a nation’s level of diversity or minority presence broadly writ unleashes racial resentment that can lead to incarceration. This article contends that population heterogeneity alone offers an incomplete picture of how ethnic-based tension can affect incarceration rates. Rather, we argue that majority ethnic groups around the world use prison systems in order to govern and manage minority populations, especially those systematically excluded from power. In addition, we argue that these political structures have their roots in a nation’s colonial legacy, a legacy that shapes a nation’s contemporary incarceration rates. Results from our quantitative analysis reveal that controlling for competing explanations, there are positive associations between ethnic political exclusion and the length and form of a nation’s colonial experience and rates of incarceration.